Edaphic mites of the cohort Gamasina (Acari: Mesostigmata) in the Botanical Garden of Nowshahr, Iran - Sepideh Saberi; Shahrooz Kazemi; Ali Ahadyiat (Persian Journal of Acarology)
A faunistic survey was carried out on edaphic mites of the cohort Gamasina in the Botanical (Ecological) Garden of Nowshahr, Mazandaran Province, Iran, since winter 2015 to winter 2016. The samples were taken from habitats randomly. A total of 34 species belonging to 20 genera, 12 families and five superfamilies were collected and identified from which the genus Gamasolaelaps Berlese, 1904 and two species, G. whartoni (Farrier, 1957) and Pergamasus brevicornis Berlese, 1903, are reported for the first time from Iran. Among the collected specimens, Gamasphis lanceolatus Karg, 1987 had the highest relative frequency (20.96%) and Pachylaelaps grandis Koroleva, 1977 and Laelaspis astronomicus (Koch, 1839) with 18.78% and 18.56% frequencies, respectively, were situated in the next ranks. Furthermore, the families Laelapidae (24.23%), Ologamasidae (21.61%) and Pachylaelapidae (20.30%) had the highest relative frequencies, respectively.